Analysis the Relationship between the Standards of Credit Assessment and Non-Performing Loans at the Gulf Commercial Bank - خلف, عمار حمد (Journal of Economics and Administrative Sciences, 2018)
This paper aims to identify the approaches used in assessment the credit applications by Iraqi banks, as well as which approach is most used. It also attempted to link these approaches with reduction of credit default and banks’ efficiency particularly for the Gulf Commercial Bank. The paper found that the Gulf Bank widely relies on the method of Judgment Approach for assessment the credit applications in order to select the best of them with low risk of default. In addition, the paper found that the method of Judgment Approach was very important for the Gulf Bank and it driven in reduction the ratio of credit default as percentage of total credit. However, it is important to say that the adoption of statistical approaches for assessment the credit applications will be useful for Gulf Bank for accurate selections the lower risk credit.